Multi Connectivity Social-Ecological System of Spiny Lobster Fisheries (Case Study: Gunungkidul Regency, Yogyakarta, Indonesia) - Lestari, Putri Agil; Adrianto, Luky; Zairion, Zairion; Zulfikar, Andi (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2023)
Spiny lobster fisheries production, provides a fairly high economic value compared to other fisheries commodities in Gunungkidul Regency. The high selling value of spiny lobsters is one of the main factors that encourage fishermen to carry out their fishing activities massively, so it can have a negative impact on the environment and spiny lobster stocks in the waters. This study aims to map the interaction and connectivity of the social-ecological system (SES) of lobster fisheries on the coast of Gunungkidul Regency. The analysis method utilized is Social-Ecological Network Analysis (SENA) with R stundio tools and Cytoscape version 3.9.1. Data were obtained from in-depth interviews using questionnaires with key informants based on purposive sampling techniques. The results of the analysis showed that there were 94 elements and 216 relationships in the basic network model of multi SES lobster fisheries. The key variables that most affect the lobster fishing network are fishing season, fishing activity, lobster stock, and fishermen's income. There needs to be synergy between the resources system (RS), resources unit (RU), resources actor (RA), and resources governance (RG) such as monitoring and evaluation from RG to other systems in order to create optimal and sustainable lobster fisheries management.